085 Ten year follow-up surveillance of paediatric acquired demyelinating syndromes (ADS) in the UK. Issue 6 (27th May 2022) - Abdel-Mannan, Omar; Absoud, Michael; Benetou, Christina; Hickson, Helga; Chong, WK; Hemingway, Cheryl; Lim, Ming; Wright, Sukhvir; Hacohen, Yael; ,
Abstract : Objective: To describe 10-year follow-up of children <16 years with acquired demyelinating syndromes (ADS) from a UK-wide prospective surveillance study. Methods: Diagnoses were retrieved from the patients' records via the patients' paediatric or adult neurolo- gist using a questionnaire. Demyelinating phenotypes, at follow-up, were classified by expert review panel. Results: 24/125 (19.2%) children, identified in the original study, were diagnosed with multiple sclerosis (MS, incidence of 2.04/million children/year); 23/24 fulfilled 2017 McDonald criteria at onset. AQP4-Ab neuromy- elitis optica spectrum disorders were diagnosed in 2/125 (1.6%, 0.26/million children/year), and relapsing MOG-Ab associated disease in 5/125 (4%, 0.43/million children/year). 4/125 seronegative non-MS patients relapsed and 85/125 (68%) remained monophasic over 10 years. 5/125 (4%) originally diagnosed with ADS were reclassified during follow-up: three children diagnosed initially with acute disseminated encepha- lomyelitis were subsequently diagnosed with acute necrotising encephalopathy (RANBP2 mutation), primary hemophagocytic lymphohistiocytosis (Munc 13–4 gene inversion) and anti-NMDA-R encephalitis. One child initially diagnosed with optic neuritis was later diagnosed with vitamin B12 deficiency, and one presenting with transverse myelitis was subsequently diagnosed with Sjögren's syndrome. Conclusions: The majority of ADS presentations in children are monophasic even at 10-year follow. Given the implications for treatment strategies, MS and CNS autoantibody mimics warrant extensive investigations. o.abdel-mannan@ucl.ac.uk|NIHR Bursary